Lesson 2 of 9 • 21 upvotes • 12:35mins
*Correction: In the first example, since the expression is XY' + X'Y + X'Y' , the output(F) of truth table in the first example should be 1110. Rest of the solution will remain same. For second example, the question is solved considering K-map has A' first and then A, similarly B' first and the B. So first box top left = A'B', second box top right = A'B third box down left=AB' fouth box down right=AB The error while explaining is extremely regretted. Thank you for your immense support & faith.
9 lessons • 1h 42m